Bibliotecas enquanto espaços de inclusão para pessoas com Síndrome de Down - Merichelo, Paula Maria Pereira (2023)
Down syndrome is one of the most prevalent disabilities in the world's population. In this context, there is a set of specific demands regarding the possibilities of support both for people with the syndrome and for those who share their routine. This study seeks to understand the perception of professional librarians about the services and information products available to people with Down Syndrome, in libraries in the city of São Carlos, in the State of São Paulo, Brazil. As a method, opinion research in human sciences was used with an exploratory and cross- sectional character, through a data collection instrument developed for the research. The participants' answers were described by simple frequency of absolute number and for the open question of the questionnaire a qualitative analysis was performed with grouping in thematic categories. The results showed that the librarians interviewed did not have specific training to meet the informational demands of people with Down Syndrome, but they are interested in seeking information and training to improve their professional practice and promote social justice and accessibility. Their suggestions included the need for continuing education on the subject and raising awareness of the class in relation to the informational specificities of all audiences. This diversity of opinions and considerations highlights the importance of promoting debate and reflection on care for people with Down Syndrome in libraries. It is essential to invest in training, interprofessional partnerships and technological resources to offer an inclusive, accessible and quality service.